(untitled) (translation. a transdisciplinary journal, 2022)
Current theories of translation and theacer, predominanrly centered in a Euro-American context, are of limited applicability co settings that are cul rurally, economically, and socio-politically different from professional and mainstream cheater spaces in the west. This paper explores the possibilities of expanding theories of cheater translation through an interrogation of actual cranslacional practices chat rake place in posccolonial and alternative performance spaces. This question is examined eh rough the transcreacions of Brechc’s work by the Wayside and Open Theatre, the first political cheater group in Sri Lanka, analyzing how they transform Brecht into powerful street performances chat scrutinize the nature of power, violence, and silence in a posccolonial space. By examining these performances, I intend to reconsider accepted notions in studies of theacer translation such as the assumed dichotomy between translator and director. The study also explores the complex modes of transference and recransference of power characterizing cheater translations in posrcolonial spaces. I will also explore the multiple variables that come into play in cheater translations in alternative cheater settings, and discuss why the term "cranscrearion" would be appropriate in identifying chis process.